Discussing sexuality with patients with neurological diseases: A survey among neurologists working in Saudi Arabia - Almalki, Daifallah Mohammed; Kotb, Mamdouh Ali; Albarrak, Anas Mohammed (Frontiers in Neurology, 2023)
Background Neurological diseases frequently affect sexual activity, and the resulting sexual dysfunction can cause much distress for patients. However, despite the importance of such complaints, neurologists frequently do not ask patients about their sexual symptoms or how their neurological illness and medications are affecting their sexual health. This study aimed to identify these difficulties as well as potential obstructions to conversations for addressing sexual dysfunction in patients with neurological diseases. Methods This cross-sectional study was performed by sending invitation letters and questionnaires to registered neurologists in Saudi Arabia. The questionnaire was constructed to determine the possibility of discussing sexual activities and function with patients with neurological diseases and the possible obstacles neurologists face in this regard. Statistical analyses were performed using the Statistical Package of Social Sciences (SPSS) program version 25, and p-values of <0.05 were considered statistically significant. Results A total of 258 of 750 neurologists (34.4%) returned the survey, of which 252 had completed the entire survey; therefore, their responses were considered suitable for further analysis. The majority of the respondents (63.1%) seldom discussed sexuality with their patients, more than half of the participants never discussed sexuality with female patients, and patients aged 60 years or older. The most commonly reported barriers were the lack of spontaneous communication by patients regarding their sexual problems (82.1%), insufficient consultation time (60.7%), and barriers based on language/culture/religion (53.6%). The majority of the respondents (61.9%) expressed the need for training on discussing sexuality as a measure that may enhance the discussion of sexual life with patients. Most of the respondents (92.9%) considered the patients responsible for bringing up problems in their sexual functioning during a patient interview. Conclusion Sexual dysfunction is rarely discussed with patients showing neurological diseases, particularly with female patients. This is due to the patient's inability to articulate their sexual problems freely as well as a lack of consultation time. Training on discussing sexuality may enhance the discussion of sexual life with patients.